2008
DOI: 10.1088/0031-9155/53/17/013
|View full text |Cite
|
Sign up to set email alerts
|

A scintillating gas detector for 2D dose measurements in clinical carbon beams

Abstract: A two-dimensional position sensitive dosimetry system based on a scintillating gas detector has been developed for pre-treatment verification of dose distributions in hadron therapy. The dosimetry system consists of a chamber filled with an Ar/CF 4 scintillating gas mixture, inside which two cascaded gas electron multipliers (GEMs) are mounted. A GEM is a thin kapton foil with copper cladding structured with a regular pattern of sub-mm holes. The primary electrons, created in the detector's sensitive volume by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…We have recently demonstrated that in an alpha particle beam (Seravalli et al 2007) and clinical carbon ion beam (Seravalli et al 2008b), the scintillating GEM detector response underestimation of the Bragg peak dose is much smaller than the one presented by state-ofthe-art 2D dosimeters with a millimeter resolution (e.g. Boon 1998a, Spielberger et al 2003.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…We have recently demonstrated that in an alpha particle beam (Seravalli et al 2007) and clinical carbon ion beam (Seravalli et al 2008b), the scintillating GEM detector response underestimation of the Bragg peak dose is much smaller than the one presented by state-ofthe-art 2D dosimeters with a millimeter resolution (e.g. Boon 1998a, Spielberger et al 2003.…”
Section: Introductionmentioning
confidence: 93%
“…The GEMs used in this work have double conical holes and are glued onto 1 mm thick Al frames. For a detailed description of the detector, we refer to (Seravalli et al 2008b).…”
Section: The Scintillating Gem Detectormentioning
confidence: 99%
See 3 more Smart Citations